Financial Literacy for Adult Learners in Community-Based Settings: A Mixed Methods Study - Edward W. Taylor; Elizabeth J. Tisdell; Karin Sprow (Adult Education Research Conference, 2010)
This paper discusses the findings of a mixed method study (282 surveys and 15 interviews) of pedagogical techniques and strategies of financial literacy educators in community based settings.